ASD, Anophthalmia and Aicardi Syndrome - Gadalla, Yousif M.; Taha, Elmuntasir (Gezira Journal of Health Sciences, 2013)
Aicardi syndrome is a rare genetic disorder, X linked dominant; the syndrome is almost exclusively seen in females. It is characterized by classic triad of agenesis of corpus collosum, infantile spasm, and chorioretinal lacune. We report a case of this rare disorder, two and half month old female child who presented with frequent episodes of seizures and multiple congenital anomalies. Examination revealed microcephaly, anophthalmia, cleft lip and palate and atrial septal defect (ASD). MRI revealed agenesis of corpus callosum and dilated ventricular system. In this paper we present a case of Aicardi Syndrome associated with anophthalmia and ASD which were not reported before. She was put on clonazepam and was having a good seizure control.